NTCDA compounds of optoelectronic interest: Theoretical insights and experimental investigation - Hssain, Ala Hamd; Gunduz, Bayram; Majid, Abdul; Bulut, Niyazi (Elsevier, 2021)
Structural, electronic, and spectroscopic properties of 1,4,5,8-naphthalene-tetracarboxylic dianhydride organic semiconductor molecule are reported based on experimental and computational methods. The spectroscopic investigations were carried out via H-1 and C-13 NMR chemical shifts and UV-VIS spectroscopy. The effects of solvation of NTCDA molecule into different solvents were investigated to explore the effect of polarities of solvents on the absorption peak of the compound. Positive charges on the Carbon atom side were discovered to be more prominent, leading to the conclusion that the NTCDA molecule could be suited for optoelectronic applications with mid-range optical band gaps.
Keywords: NTCDA; Bandgap energy; Optoelectronic parameters; Density functional theory; Hartree-Fock; FTIR; UV-Vis; NMR